Unmet Health and Childcare Needs after Neonatal Intensive Care Unit Discharge - Younge, Tamiko; Jacobs, Marni; Soghier, Lamia; Fratantoni, Karen (American Journal of Perinatology, 2025)
This study aimed to identify unmet health and childcare needs and associations with infant characteristics, parent characteristics, and parent self-efficacy after neonatal intensive care unit (NICU) discharge.We conducted a secondary mixed-methods analysis of data from a single-center randomized control trial. Twelve months after discharge, parents reported if their child did not need, need and received, or needed but did not receive seven health and childcare services. Associations with infant characteristics, parent characteristics, and parent self-efficacy were assessed using logistic regression. Open-ended responses were analyzed for themes.A total of 241 families completed assessments 12 months after discharge. Thirty-three respondents (14%) reported at least one unmet need. Increasing gestational age decreased the odds of unmet needs (odds ratio [OR]: 0.91; 95% confidence interval [CI]: 0.84–0.97), while longer length of stay and moderate or severe infant functional status increased odds (OR: 1.01; 95% CI: 1.01–1.02; OR: 2.93; 95% CI: 1.14–8.17). Greater self-efficacy was associated with lower odds of unmet needs (OR: 0.91; 95% CI: 0.85–0.97). Black parents had 2.8 times the odds of unmet needs compared to White parents after adjusting for length of stay (95% CI: 1.15–7.54). Self-efficacy may have a moderating effect on this racial disparity. Parents reported needing childcare, psychosocial support, and financial assistance in open-ended responses.We found families experienced unmet health and childcare needs with evident racial disparities in the year after NICU discharge. Greater parental self-efficacy may reduce this racial gap. Pediatric practices and health care systems, especially NICU follow-up programs, should continue to screen and connect this high-risk population to support and resources.
Keywords: parent self-efficacy; NICU follow-up; health disparities; children with special health care needs